Information Epidemics and the Transformation of Science - Dufour, Christine; Tabah, Albert N. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
The purpose of the present paper is to characterize the literatures of information epidemics, to analyze how the intellectual structure of a research specialty is transformed as a result of a major discovery, and to describe how scientists respond to rapidly changing conditions in their specialty. A recent study of the physics literature in the 1970s and 1980s has identified high temperature. . .